Andhakārera Āndāmāne : nrtattvamūlaka bhramaṇa-kāhinī - Bhattacharya, Asutosh, 1909- (E. Mukhārji, 1983)
History and sociology of the Andaman and Nicobar Islands with special reference to the Onge and Jarawa people in the Islands; based on a 1949 travel by an anthropologist.